FREQUENCY ANALYSIS OF SINGULAR FIRST-PERSON PRONOUNS AND VERBS IN THE UTTERANCES OF SCHIZOPHRENIA PATIENTS AND HEALTHY CONTROLS. A RESEARCH REPORT - Obrębska, Monika (Lingua Posnaniensis, 2013)
The purpose of this article is to present the results of a frequency analysis of first-person pronouns and verbs in utterance texts of schizophrenia patients and healthy controls. Method: The study involved 130 hospitalized psychiatric patients diagnosed with paranoid schizophrenia and 130 healthy individuals. As a result of the study, the largest corpus to date of marked utterance texts of schizophrenic patients in the Polish language was obtained. The ratio of the number of singular first-person personal pronouns and verbs to the total number of personal pronouns and verbs used in any particular text was calculated and was then averaged for each of the four studied groups: a group of patients with positive schizophrenia symptoms, a group of patients with negative schizophrenia symptoms, a control group for the patients with positive symptoms, and a control group for the patients with negative symptoms. Results: The highest mean was found for the group of patients with positive schizophrenia symptoms, and the lowest for the group of healthy individuals. This difference was found to be statistically significant. Conclusion: The “egocentric orientation” and difficulty in defining one’s own identity experienced by psychotic patients, especially those with the positive type of schizophrenia, are reflected in their lexical choices.